The effects of stress toward employee performance in UK Trade Department, Scope International (M) Sdn Bhd / Mohamed Rahshafeez Rahmat Ali - Rahmat Ali, Mohamed Rahshafeez (Faculty of Business and Management, 2010)
This study is focus on the stress issues at Scope International (M) Sdn. Bhd. which has potential to affect employees’ performance. The main objective of this project paper is identifying the main factor that contributes to stress issues towards employees’ performance in Scope International (M) Sdn. Bhd. The research is focusing on employees at Scope International (M) Sdn. Bhd., which is consisting of 40 respondents from UK Trade Department only. The theoretical framework of this study consists of dependent variable and independent variables. The dependent variable is employees’ performance while the independent variables are work tasks, working environment, and organization rules and procedure. Data collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The analysis includes the reliability, frequency distribution, descriptive analysis, and correlation.